Long‐term survival analysis of patients with non‐small cell lung cancer complicated with type 2 diabetes mellitus. Issue 5 (19th March 2020) - Wang, Gaoxiang; Li, Xuejiao; Xiong, Ran; Wu, Hanran; Xu, Meiqing; Xie, Mingran
Abstract : Background: This study aimed to investigate the effect of type 2 diabetes mellitus on survival of patients with non‐small cell lung cancer (NSCLC). Methods: We retrospectively analyzed NSCLC patients who had undergone radical lung cancer surgery from January 2011 to December 2014 in the Anhui Medical University affiliated Anhui Provincial Hospital. Kaplan‐Meier plots, log‐rank tests, and Cox proportional hazards regression models were used to describe the effect of type 2 diabetes mellitus on the overall survival of patients with NSCLC. Results: A total of 769 patients with NSCLC were enrolled, including 126 in the diabetic mellitus group and 643 in the nondiabetic mellitus group. The one, three, and five‐year survival for patients with and without diabetes mellitus were 86.1% versus 89.6%, 49.5% versus 62.4%, and 33.3% versus 40.6%, respectively. The Cox model showed that type 2 diabetes mellitus was a poor independent prognostic factors for NSCLC patients. In addition, metformin is a good independent prognostic factor for patients with non‐small cell lung cancer with type 2 diabetes mellitus. Conclusions: NSCLC patients without type 2 diabetes mellitus have an increased survival rate compared with those with type 2 diabetes mellitus.